Patriot Number One: American Dreams in Chinatown - Lauren Hilgers (Crown, 2018)
In 2014, in a snow-covered house in Flushing, Queens, a village revolutionary from Southern China considered his options. Zhuang Liehong was the son of a fisherman, the former owner of a small tea shop, and the spark that had sent his village into an uproar—pitting residents against a corrupt local government. Under the alias Patriot Number One, he had stoked a series of pro-democracy protests, hoping to change his home for the better. Instead, sensing an impending crackdown, Zhuang and his wife, Little Yan, left their infant son with relatives and traveled to America. With few contacts and only a shaky grasp of English, they had to start from scratch.